Evaluating the Effectiveness of Community-Based Mangrove Rehabilitation Initiatives - Mardhiansyah, Muhammad; Suhada, Nur; Sribudiani, Evi; Amraini, Said Zul; Farhan, Hafid (Heca Sentra Analitika, 2025)
Management actions through rehabilitation activities can restore mangrove ecosystems by involving community participation. This study aims to determine the involvement and effectiveness of community-based rehabilitation activities. This study was conducted in Teluk Pambang Village, Bengkalis Regency. The method used is qualitative, with a purposive sampling technique based on certain criteria. The data analysis used is qualitative descriptive and data processing using nvivo 12 plus software. The research findings explain that the dominant factors that encourage people to carry out mangrove rehabilitation activities are based on additional income, strengthening the issue of carbon trade economy, kinship elements, and easy access to financing through donors. The level of program understanding, target accuracy, activity management, and real changes are the most effective rehabilitation activities for the community. At the same time, the indicators for achieving goals are still considered ineffective.